Exogenous myo-inositol enhances drought tolerance in maize seedlings by antioxidant defense, and photosynthetic efficiency - Liu, Yuqi; Sun, Hao; Guo, Xiaonan; Song, Tianyuan; Yu, Zongling; Li, Wei; Lin, Yaxin; Zhou, Yanci; Yang, Deguang (Frontiers in Plant Science, 2025)
IntroductionDrought stress severely impairs maize (Zea mays L.) production, particularly during the seedling stage.MethodsIn this study, we aimed to investigate the role of exogenous myo-inositol (MI) in alleviating drought stress in maize seedlings. We established four treatments: control (CK), MI application under normal irrigation (G), drought stress (D), and MI application under drought stress (DG).ResultsThe results demonstrate that MI significantly restored growth parameters under drought conditions, increasing shoot and root biomass by 40.74% and 28.30%, respectively, on Day 7. Additionally, MI enhanced photosynthetic efficiency (net photosynthetic rate (Pn), transpiration rate (Tr), stomatal conductance (gs), and photosystem II efficiency (Fv/Fm)) and upregulated osmotic regulators (e.g. proline and soluble sugars) in the leaves and roots. Furthermore, antioxidant enzymes (superoxide dismutase (SOD), peroxidase (POD), and glutathione reductase (GR)) and ascorbic acid–glutathione (ASA–GSH) cycle components were synergistically activated by MI, reducing oxidative damage, as indicated by decreases in malondialdehyde (MDA), H2O2, and O2·-. Principal component analysis highlighted the pivotal roles of osmotic adjustment and antioxidant systems in drought mitigation.DiscussionThese findings reveal that MI is a potent inducer of drought resilience in maize, offering a novel strategy for maize cultivation under water scarcity.